Revisiting Rainwater Harvesting: A Systematic Review of Management Practices in Malaysia Using PRISMA - Shamsuddin, Mohd.Suhaimi; Yusof, Mohamad Nizam; Hamat, Zahri (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
This study revisits the development and application of rainwater harvesting (RWH) systems in Malaysia and highlights their role in integrated and sustainable urban water resource management. A systematic literature review based on PRISMA guidelines analyzes research on RWH, storm-water management, and green technologies in Asia, especially Malaysia. The results show that RWH has evolved from a traditional practice to a modern multifunctional solution for water conservation, flood protection, and climate change adaptation. Considering the Malaysian conditions, the unique RWH system is an important tool for reducing flash floods, improving groundwater recharge, and reducing storm-water pollution. The study recommends using green infrastructure, such as rain gardens, as a complementary solution to improve water retention and quality. This highlights the need for local, cost-effective technical and regulatory frameworks to facilitate the widespread adoption of RWH. This study also encourages the integration of RWH into national policies to achieve sustainable water management in line with the Sustainable Development Goals. The novelty of this study lies in its systematic review approach, focusing on the evolution of water resource management strategies in Malaysia and the need for integrated planning and policy support to take full advantage of the potential of the RWH system to address water and environmental issues in Malaysia.